2020
DOI: 10.1038/s41598-020-75456-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of lithium metal dendrites with ceramic solid electrolyte

Abstract: Dendrite formation, which could cause a battery short circuit, occurs in batteries that contain lithium metal anodes. In order to suppress dendrite growth, the use of electrolytes with a high shear modulus is suggested as an ionic conductive separator in batteries. One promising candidate for this application is Li7La3Zr2O12 (LLZO) because it has excellent mechanical properties and chemical stability. In this work, in situ scanning electron microscopy (SEM) technique was employed to monitor the interface behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 32 publications
(52 reference statements)
2
57
0
Order By: Relevance
“…Golozar et al [42] performed a chemical analysis of the cross-section of the Li-metal anode and the polymer electrolyte, showing the presence of salt in the vicinity of the isles formed on the anode and inhomogeneous salt distribution in the polymer, respectively. EDS mapping of symmetrical Li cells with LLZO electrolyte has also shown differences in the Li thickness on the anode, as well as the inhomogeneous distribution of Zr, La, and C in the cross-section of the electrolyte reported by Golozar et al [38].…”
Section: Chemical and Crystallographic Analysismentioning
confidence: 68%
See 4 more Smart Citations
“…Golozar et al [42] performed a chemical analysis of the cross-section of the Li-metal anode and the polymer electrolyte, showing the presence of salt in the vicinity of the isles formed on the anode and inhomogeneous salt distribution in the polymer, respectively. EDS mapping of symmetrical Li cells with LLZO electrolyte has also shown differences in the Li thickness on the anode, as well as the inhomogeneous distribution of Zr, La, and C in the cross-section of the electrolyte reported by Golozar et al [38].…”
Section: Chemical and Crystallographic Analysismentioning
confidence: 68%
“…Figure 1 shows the different dendrite morphologies reported using SEM. Golozar et al [38] also observed dendrites with mossy and needle morphologies in a symmetrical Li-metal cell with Li 7 La 3 Zr 2 O 12 (LLZO) electrolyte. This study showed the formation and growth of the dendrites on the Li electrode from regions that thinning of the anode and consumption of Li had occurred [38].…”
Section: Morphological Analysismentioning
confidence: 94%
See 3 more Smart Citations